The Cogeco Case: The First Preliminary Ruling on the Private Enforcement Directive - Catarina Vieira Peres (Market and Competition Law Review)
In March this year, the European Court of Justice (hereinafter “CJ”) answered the first preliminary question regarding the Private Enforcement Directive (“Directive”).1 One might expect this decision2 to remain relevant for the next few years, as it sheds some light on the rather intricate issue of the Directive’s temporal application. The CJ explains what rules are applicable to actions for damages regarding infringements which occurred prior either to the Directive’s adoption or to its implementation in the respective Member States. The case is also of major interest since it illustrates the role that the principle of effectiveness can play when applied alongside Articles 101 or 102 of the Treaty on the Functioning of the European Union (“TFEU”).3 Finally, albeit not expressly addressed, the case is also of interest regarding the controversial issue of parent company liability in private enforcement, where it represents a novelty in the Portuguese legal order.